Strain-Dependent Variations in Spatial Learning and in Hippocampal Synaptic Plasticity in the Dentate Gyrus Of Freely Behaving Rats - Manahan-Vaughan, Denise; Schwegler, Herbert (Frontiers in Behavioral Neuroscience, 2011)
Hippocampal synaptic plasticity is believed to comprise the cellular basis for spatial learning. Strain-dependent differences in synaptic plasticity in the CA1 region have been reported. However, it is not known whether these differences extend to other synapses within the trisynaptic circuit, although there is evidence for morphological variations within that path. We investigated whether Wistar and Hooded Lister (HL) rat strains express differences in synaptic plasticity in the dentate gyrus in vivo. We also explored whether they exhibit differences in the ability to engage in spatial learning in an eight-arm radial maze. Basal synaptic transmission was stable over a 24-h period in both rat strains, and the input–output relationship of both strains was not significantly different. Paired-pulse analysis revealed significantly less paired-pulse facilitation in the HL strain when pulses were given 40–100 ms apart. Low frequency stimulation at 1 Hz evoked long-term depression (>24 h) in Wistar and short-term depression (<2 h) in HL rats; 200 Hz stimulation induced long-term potentiation (>24 h) in Wistar, and a transient, significantly smaller potentiation (<1 h) in HL rats, suggesting that HL rats have higher thresholds for expression of persistent synaptic plasticity. Training for 10 days in an eight-arm radial maze revealed that HL rats master the working memory task faster than Wistar rats, although both strains show an equivalent performance by the end of the trial period. HL rats also perform more efficiently in a double working and reference memory task. On the other hand, Wistar rats show better reference memory performance on the final (8–10) days of training. Wistar rats were less active and more anxious than HL rats. These data suggest that strain-dependent variations in hippocampal synaptic plasticity occur in different hippocampal synapses. A clear correlation with differences in spatial learning is not evident however.